Elastic Tethers Between Separating Anaphase Chromosomes Regulate the Poleward Speeds of the Attached Chromosomes in Crane-Fly Spermatocytes - Forer, Arthur; Berns, Michael W. (Frontiers in Molecular Biosciences, 2020)
Elastic tethers connect separating anaphase chromosomes in most or all animal cells. We tested whether tethers are involved in coordinating movements of separating chromosomes in anaphase crane-fly spermatocytes. In these cells the movements of separating chromosomes are coupled, but they become uncoupled after the tethers are severed by laser microbeam irradiation of the interzone region between the chromosomes (Sheykhani et al., 2017). While this strongly suggests that the tethers are involved with coordinating the poleward chromosome movements of the separating chromosomes, the experiments are open to another interpretation: the laser irradiation indeed cuts the tethers but it also might damage something else in the interzone. Thus it might be that chromosome movements are regulated by the other component(s), not the tethers. In the experiments reported herein we distinguish between those two possibilities by cutting the arms from individual chromosomes. Separating the arms from the chromosomes breaks the mechanical connection between the separating chromosomes and thereby disables the tethers without damaging components in the interzone. In the experiments reported herein, disabling tethers in this way uncoupled the movements of the separating chromosomes. We conclude that tethers are involved in regulating the speeds of separating anaphase chromosomes in crane-fly spermatocytes